Донозологическая диагностика болезней органов дыхания у жителей мегаполиса металлургического профиля - Гребняк, Н. П.; Федорченко, Р. А.; Гребняк, Микола Петрович; Федорченко, Руслана Анатоліївна (My University, 2015)
The aim of this work was to study the functional state of the respiratory system in metropolitan population of metallurgical profile as a result of screening spirography. Materials and methods. Characteristics of air pollution has been studied according to the total emissions for 1990-2013. Were examined 381 resident of Zaporozhye: 217 women, 164 men (mean age 43,65±1,13 years). The study of the functional state of pulmonary ventilation capacity was conducted using electronic spiroanalizatorov (RID 124-D and SPIROKOM HAI-Medica) recording curve "flow-volume". Respiratory function was evaluated in terms of: forced vital capacity of the lungs, forced expiratory volume in 1 second, the index Tiffno, volume maximum ventilation of the lungs, life volumetric expiratory flow at 25%, 50% and 75% FVC, average volumetric expiratory flow rate in the range of 25 -75% FVC, peak volume forced expiratory flow, residual volume of the lungs. Revealed the presence of disturbances ventilation function and determine their type (obstruction, restriction, mixed). Statistical processing was performed using «Statistica 6,0». The study revealed: 53,8±2,5 % of the industrial city residents observed deviations ventilation function of the upper respiratory tract, there are gender differences, consisting of a greater prevalence among men (p<0,05), with age significantly increases the proportion weight donozological states of respiratory function, especially in the 30-39 and 40-49 years.
Keywords: спирография; загрязнение атмосферного воздуха; Respiratory System; Respiratory Function Tests; Air Pollution